Prevalence of Onychomycosis in the Psoriatic Patients in a Tertiary Care Hospital, Chennai, Tamil Nadu, India - K. Sangeetha; K.S. Sridharan; S Murugan; P Kennedy Kumar (National Journal of Laboratory Medicine, 2019)
Introduction: Psoriasis is a common chronic hyper proliferative skin disorder, with involvement of nail in about 25% patients. Onychomycosis is the fungal infection of the nail which also affects the psoriatic patients and thereby increasing disfigurement of nail in already clinically affected condition. Aim: To know the prevalence of onychomycosis in psoriatic patient with nail involvement. To determine the mycological profile of onychomycosis in psoriasis patient and to perform the antifungal susceptibility testing for the fungus isolated. Materials and Methods: A cross-sectional study was done for period of one year in a tertiary care center after obtaining institutional ethical clearance. Nail scrapings were taken after proper disinfection and subjected to KOH and cultured in Sabouraud's dextrose agar and Dermatophyte test medium and incubated upto four weeks. Tubes which were showing growth were further processed for identification of species and antifungal susceptibility test was done. Tubes which did not show growth at the end of four weeks were reported as no growth. Results: Total number of samples was 86. We had around 61.62% of males and rest were females. Most of our patients were in the age group of 51 to 70 years. Four out of 86 samples grew fungus of which two were Candida tropicalis and Fusarium oxysporum and Alternaria alternata. There was no dermatophyte isolated. We did not encountered any resistance. Conclusion: It is better to screen for fungal infection of nails in psoriatic patients with nail involvement. As the fungal infection will cause more destruction and disfigurement, appropriate antifungal therapy if started early will have better clinical outcome.